Differences in the Effect of Offline, Blended, and Online Learning in Statistics Learning on Physical Education Students - Rumahlewang, Emma; Ratnaya, I Gede; Matitaputty, Johanna (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The purpose of this study was to analyze the difference in the effect of learning carried out face-to-face directly or offline, learning carried out offline, online and blended learning. The research method was a quantitative method with a design experiment. This research was conducted in Ambon city, Maluku-Indonesia. The population in this study amounted to 118 Physical Education Student Sampling was carried out randomly to obtain the number of samples using Slovin's formula: n=n/(1+ne2) = 74. Instrument used in this research is an essay test. The test scores from the two sessions were combined to get a total score of statistical learning outcome scores were analyzed using one-way ANOVA, but before being analyzed the scores were tested for requirements with homogeneity tests. Â The results of this study indicate that the learning carried out provides an overview of the different statistics learning outcomes based on the results of the F test with an F value of 7.131 and a p-value of 0.02. Based on the post-hoc follow-up test, it was found that the student taught by face-to-face or offline learning got better statistics learning outcomes than the students taught online, with a p-value of 0.02. Meanwhile, offline student statistics learning outcomes are not significantly better than student statistics learning outcomes taught using mixed methods or blended learning. Then, the statistics learning outcomes of students taught by mixed learning are not significantly better than online statistics learning outcomes. Thus, it can be said that learning that is carried out offline or face-to-face directly (Blended Learning) is still better and superior to learning that is carried out in Blended Learning and which is carried out online.